Write in the correct coefficients for the balanced equation:
__CH4 + __O2 → __CO2 + __H2O
9 answers
1CH4 + 2O2 → 1CO2 + 2H2O
what is the chemical reaction for
C4H8 + O2 → 4CO2 + 4H2O
decomposition
synthesis
combustion
double displacement
single displacement
C4H8 + O2 → 4CO2 + 4H2O
decomposition
synthesis
combustion
double displacement
single displacement
The chemical reaction
C4H8 + O2 → 4CO2 + 4H2O
is an example of combustion.
C4H8 + O2 → 4CO2 + 4H2O
is an example of combustion.
If x= root 5- root 3 upon root 5+root 3, evaluate x+y=
To evaluate the value of x, we use the conjugate of the denominator which is (root 5 - root 3)
So x = (root 5 - root 3) / (root 5 + root 3) * (root 5 - root 3) / (root 5 - root 3)
x = ((root 5)^2 - (root 3)^2) / ((root 5)^2 - (root 3)^2)
x = (5 - 3) / (5 - 3)
x = 2
We are not given any value for y, so we cannot determine its value.
So x = (root 5 - root 3) / (root 5 + root 3) * (root 5 - root 3) / (root 5 - root 3)
x = ((root 5)^2 - (root 3)^2) / ((root 5)^2 - (root 3)^2)
x = (5 - 3) / (5 - 3)
x = 2
We are not given any value for y, so we cannot determine its value.
And y's value was root 5 + root 3 upon root 5- root 3 now calculate the question
Now that we have the value of x (which is 2) and the value of y (which is (root 5 + root 3) / (root 5 - root 3)), we can evaluate the expression x+y as follows:
x + y = 2 + ((root 5 + root 3) / (root 5 - root 3))
To simplify this expression, we can rationalize the denominator as follows:
x + y = 2 + ((root 5 + root 3) / (root 5 - root 3)) * ((root 5 + root 3) / (root 5 + root 3))
x + y = 2 + ((5 + 2root 15 + 3) / (5 - 3))
x + y = 2 + (8 + 2root 15)
Therefore, x + y = 10 + 2root 15.
x + y = 2 + ((root 5 + root 3) / (root 5 - root 3))
To simplify this expression, we can rationalize the denominator as follows:
x + y = 2 + ((root 5 + root 3) / (root 5 - root 3)) * ((root 5 + root 3) / (root 5 + root 3))
x + y = 2 + ((5 + 2root 15 + 3) / (5 - 3))
x + y = 2 + (8 + 2root 15)
Therefore, x + y = 10 + 2root 15.
If x= root 5 - root 3 upon root 5 + root 3 and y= root 5 + root3 upon root 5- root 3, evaluate x+y
To solve this problem, we need to rationalize the denominators of x and y so that we can add them together.
Starting with x:
x = (root 5 - root 3) / (root 5 + root 3)
x = [(root 5 - root 3) / (root 5 + root 3)] * [(root 5 - root 3) / (root 5 - root 3)]
x = (5 - 3 - 2root 15) / (5 - 3)
x = -1 + root 15
Next, let's simplify y in the same way:
y = (root 5 + root 3) / (root 5 - root 3)
y = [(root 5 + root 3) / (root 5 - root 3)] * [(root 5 + root 3) / (root 5 + root 3)]
y = (5 + 3 + 2root 15) / (5 - 3)
y = 4 + 2root 15
Now we can add x and y together:
x + y = (-1 + root 15) + (4 + 2root 15)
x + y = 3 + 3root 15
Therefore, the value of x+y is 3 + 3root 15.
Starting with x:
x = (root 5 - root 3) / (root 5 + root 3)
x = [(root 5 - root 3) / (root 5 + root 3)] * [(root 5 - root 3) / (root 5 - root 3)]
x = (5 - 3 - 2root 15) / (5 - 3)
x = -1 + root 15
Next, let's simplify y in the same way:
y = (root 5 + root 3) / (root 5 - root 3)
y = [(root 5 + root 3) / (root 5 - root 3)] * [(root 5 + root 3) / (root 5 + root 3)]
y = (5 + 3 + 2root 15) / (5 - 3)
y = 4 + 2root 15
Now we can add x and y together:
x + y = (-1 + root 15) + (4 + 2root 15)
x + y = 3 + 3root 15
Therefore, the value of x+y is 3 + 3root 15.